A peculiar Roman context in Vicenza: A new approach on Pottery and Amphorae - Mazzocchin, Stefania; Furlan, Guido (Rei Cretariae Romanae Fautorum Acta, 2017)
The analysis of the amphora contexts recovered in Vicenza allows to understand which foodstuffs were imported and consumed in the town, and also which were the different conditions of use of the amphoras for draining and stability purposes. Among all the contexts found in Vicenza, Contrà della Piarda allowed to examine the relationship between an earthwork and the artefacts, with the intent to find out information on earthwork chronology.